Aktivitas Antijamur Ekstrak Kecombrang (Etlingera elatior) Terhadap Aspergillus Flavus FNCC 6109 - Rizky Nasution, Yovanda; Selamet Duniaji, Agus; Indri Hapsari Arihantana, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 2 (2020): Jurnal ITEPA, 2020)
The aim of this research was to determine the concentration of phenol compounds and antifungal activity of torch ginger (Etlingera elatior) on Aspergillus flavus FNCC 6109. This research was a completely randomized design with 10 concentrations of shoot, flower, and fruit extract which were 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, and 100%. The data were analyzed with variance analysis then followed by Duncan Multiple Range Test (DMRT). Analysis were repeated 2 times resulting in 20 experimental units. Result showed that each concentration of shoot, flower, and fruit extract had significantly effect (P<0,05) in inhibition of Aspergillus flavus FNCC 6109. Shoot, flower, and fruit extract of torch ginger contained phenol compounds of 154,56 mgGAE/g, 127,22 mgGAE/g, and 261,52 mgGAE/g. The best antifungal activity for shoot extract of torch ginger was at 70% concentration with a diameter inhibition of 7,9 mm category medium, for flower extract of torch ginger was at 90% concentration with a diameter inhibition of 5,65 mm category medium, and for fruit extract of torch ginger was at 80% concentration with a diameter inhibition of 13,75 mm category strong. Fruit extract of torch ginger had the highest phenol compound which could inhibit Aspergillus flavus FNCC 6109. Keywords : phenol, torch ginger, antifungal, Aspergillus flavus.